The luck uglies - Durham, Paul (Paul Joseph), 1972- (Harper, 2015)
Growing up playing in the streets and on the rooftops of Village Drowning, Rye O'Chanter and her friends never took the stories of the Bog Noblins seriously, until one night they meet one out in the swamps--and that meeting takes them to the Luck Uglies, the ancient society that protects their Village Drowning.